Defense mechanism in Charles Williams’ Dead Calm - Kurniasari, Atika Rahma; Syaikhu, Akhmad; Fanani, Abu; Rohman, Abdur; Frank, Ahmad (Jurnal Langua, 2024)
This study analyzes defense mechanism undergone by Hughie Warriner in Dead Calm. Warriner conducts defense mechanism because he wants to reduce his anxiety after accidental incident of sinking a yacht and the killing of his friend. His action of doing defense mechanism is psychologically explainable that is also undergone by people in real life which then becomes the reason the researchers get interested in analyzing defense mechanism. Besides, this kind of mechanisms are close in human life that man is born with anxiety through which he conducts defense mechanisms unconsciously. Using three types of anxiety by Sigmund Freud, the study shows that Warriner conducts defense mechanisms: denial, displacement, and sublimation. By denial, he denies sinking the yacht and killing his friend, by displacement, he blames other object by shouting at it, and by sublimation, he puts the investigators under the yacht. Thus, the three types of defense mechanism are worthy of research since people can reduce their anxiety properly. By this study then, the researchers hope so much that it contributes to the development of the literary study especially in the study of psychology of literature.